2013
DOI: 10.2174/138527213805289204
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Based Microcapsule Materials - Their Preparation and Physiochemical Properties

Abstract: Microencapsulation is a technique devoted to entrapping core material inside one or more polymeric coatings. Cyclodextrins (CDs) and its various derivatives are used as functional building blocks because of their unique physical properties. As well CDs possess, the ability to form well-defined host/guest inclusion complexes with lipophilic guests in aqueous solution or polar organic solvents. This review covers literature over the past decade concerning the design of microcapsules containing CDs and their phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In recent years, a relatively large number of generalist reviews has been published on practically all of these aspects of CDs, so many that it would not be feasible to cite them all. I chose to highlight those that concern research in chemistry and macromolecular chemistry, supramolecular chemistry, catalysis, , membranes, , aromas, foods, , agrochemistry, biotechnology, enzyme technology, cosmetics, , pharmacy and medicine, textiles, , chromatography, microencapsulation, nanotechnologies, click chemistry, analytical chemistry, remediation, , and decontamination. , Several books (Table ) ,,,,, and series can also be consulted on the different aspects of CDs including their description, characterization, properties, derivatives, supramolecular chemistry, and applications.…”
Section: Cyclodextrins – Present Situation Trends and Outlook: Person...mentioning
confidence: 99%
“…In recent years, a relatively large number of generalist reviews has been published on practically all of these aspects of CDs, so many that it would not be feasible to cite them all. I chose to highlight those that concern research in chemistry and macromolecular chemistry, supramolecular chemistry, catalysis, , membranes, , aromas, foods, , agrochemistry, biotechnology, enzyme technology, cosmetics, , pharmacy and medicine, textiles, , chromatography, microencapsulation, nanotechnologies, click chemistry, analytical chemistry, remediation, , and decontamination. , Several books (Table ) ,,,,, and series can also be consulted on the different aspects of CDs including their description, characterization, properties, derivatives, supramolecular chemistry, and applications.…”
Section: Cyclodextrins – Present Situation Trends and Outlook: Person...mentioning
confidence: 99%
“…The hydrogen bonding below and above the ring leads to secondary belts which increases the rigidity of the b-CD and hence causes low solubility. 21 In contrast, a-CD and g-CD do not have secondary belts hence their structures are exible and are therefore very soluble due to the availability of free hydroxyl groups. It has been reported that that hydrogen bonding assists the threading of CD along the chain of the guest molecule.…”
Section: Preparation Of Dispersed Cd-tetradecane Ic Microrodsmentioning
confidence: 99%
“…Recent research on CD is also very active in environmental fields such as water and wastewater treatment. Different comprehensive reviews [ 12 , 13 , 14 , 15 , 16 ] have been reported on this topic.…”
Section: Introductionmentioning
confidence: 99%